The Influence of Family Environment and School Environment on Civics Learning Outcomes of Class VIII Students at SMP Negeri 29 Pekanbaru - Syafniati, Della; Gimin, Gimin; Hardian, Mirza (FKIP - Universitas Riau, 2024)
This research was motivated by the poor condition of the family environment and school environment that affected Civics Learning outcomes. This study aims to determine the influence of the family environment and school environment on the learning outcomes of Civics grade VIII students at SMP Negeri 29 Pekanbaru. This study used a quantitative approach with an associative method of causal relationships. The results showed that the value of the family environment was in the good category with a percentage of 71%. The school environment is in the good category with a percentage of 73%. Meanwhile, the learning outcomes of Civics grade VIII students are included in the poor category with a percentage of 63.6%. The family environment and school environment affect the learning outcomes of civics at SMP Negeri 29 Pekanbaru with a value of Fcalculate 50.454 > Ftable 3.18 and significant of 0.000 < 0.05. The contribution of variables X1 and X2 to Y contributed 66% while the other 34% was influenced by other variables not discussed in this study.